If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2 = x + 2(x + -1) + 4 Reorder the terms: 2 + 3x = x + 2(x + -1) + 4 Reorder the terms: 2 + 3x = x + 2(-1 + x) + 4 2 + 3x = x + (-1 * 2 + x * 2) + 4 2 + 3x = x + (-2 + 2x) + 4 Reorder the terms: 2 + 3x = -2 + 4 + x + 2x Combine like terms: -2 + 4 = 2 2 + 3x = 2 + x + 2x Combine like terms: x + 2x = 3x 2 + 3x = 2 + 3x Add '-2' to each side of the equation. 2 + -2 + 3x = 2 + -2 + 3x Combine like terms: 2 + -2 = 0 0 + 3x = 2 + -2 + 3x 3x = 2 + -2 + 3x Combine like terms: 2 + -2 = 0 3x = 0 + 3x 3x = 3x Add '-3x' to each side of the equation. 3x + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 0 = 3x + -3x Combine like terms: 3x + -3x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| (2x-1)(x+6)=24 | | 5(5t-2-2)=-35 | | 36x+8x=1x+76 | | 6(1-6x)-4(-1-x)=10 | | 10/16+17/16q=12/16+3/16q | | r/3=9 | | 36x+8x=1x+72 | | -4x-5=-(x-4) | | -4(3x+2)=x+2(x-1) | | 8(5x-6)=152 | | 2x=8+y | | -18+12x=10x+14 | | -8=-(4)+4 | | =x^4-4x^3+3x^2-4x+2 | | 11.95x+4.95=64.70 | | 7=m/2 | | 11-8x=75-36x | | 8p^2-2p+15=0 | | -2x+y=-8 | | 4n-1=-29 | | 0.5y=-6 | | 7-3(p+5)=27 | | 56x^3/(42x^2) | | 3(6-b)-33=27b-5(3+6b) | | 58+11x=6x+92 | | Mx+mx=p | | 3(4x+3)-8=13 | | -0.4x+20=-16 | | a=-10+2b | | 3x-4=4(x+3) | | 3.5x+8=x | | m-6m=8 |